Traditional healing practices in rural Bangladesh: a qualitative investigation - Md. Imdadul Haque; A. B. M. Alauddin Chowdhury; Md. Shahjahan; Md. Golam Dostogir Harun (BMC Complementary and Alternative Medicine, 2018)
Abstract Background Traditional healing practice is an important and integral part of healthcare systems in almost all countries of the world. Very few studies have addressed the holistic scenario of traditional healing practices in Bangladesh, although these serve around 80% of the ailing people. This study explored distinctive forms of traditional healing practices in rural Bangladesh. Methods During July to October 2007, the study team conducted 64 unstructured interviews, and 18 key informant interviews with traditional healers and patients from Bhabanipur and Jobra, two adjacent villages in Chittagong district, Bangladesh. The study also used participatory observations of traditional healing activities in the treatment centers. Results Majority of the community members, especially people of low socioeconomic status, first approached the traditional healers with their medical problems. Only after failure of such treatment did they move to qualified physicians for modern treatment. Interestingly, if this failed, they returned to the traditional healers. This study identified both religious and non-religious healing practices. The key religious healing practices reportedly included Kalami, Bhandai, and Spiritual Healing, whereas the non-religious healing practices included Sorcery, Kabiraji, and Home Medicine. Both patients and healers practiced self-medication at home with their indigenous knowledge. Kabiraji was widely practiced based on informal use of local medicinal plants in rural areas. Healers in both Kalami and Bhandari practices resorted to religious rituals, and usually used verses of holy books in healing, which required a firm belief of patients for the treatment to be effective. Sorcerers deliberately used their so-called supernatural power not only to treat a patient but also to cause harm to others upon secret request. The spiritual healing reportedly diagnosed and cured the health problems through communication with sacred spirits. Although the fee for diagnosis was small, spiritual healing required different types of treatment instruments, which made the treatment implicitly expensive. Conclusions Traditional healing was widely practiced as the means of primary healthcare in rural areas of Bangladesh, especially among the people with low socioeconomic status. The extent of services showed no decline with the advancement of modern medical sciences; rather it has increased with the passage of time.